1998
DOI: 10.1152/ajpcell.1998.274.3.c557
|View full text |Cite
|
Sign up to set email alerts
|

Capacitative Ca2+ entry is involved in cAMP synthesis in mouse parotid acini

Abstract: Muscarinic receptor interaction leading to augmentation of isoproterenol-stimulated cAMP accumulation in mouse parotid acini involves Ca2+ (28). The effectiveness of capacitative Ca2+entry and intracellular Ca2+release on this response was determined in time course studies by using three independent tools to manipulate the free intracellular Ca2+ concentration: the muscarinic agonist carbachol, thapsigargin, and ionomycin. Time course studies revealed that Ca2+ release from intracellular stores by carbachol pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
40
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 34 publications
5
40
0
Order By: Relevance
“…The marked reduction of the inhibitory action of thapsigargin in the absence of added Ca 2+ and in the presence of EGTA indicates that Ca 2+ released from intracellular stores plays only a minor role in inhibition of cyclic AMP accumulation, at most. This is consistent with the conclusion drawn from experiments on HEK 293 cells transfected with the type VI (Cooper et al, 1994) and type VIII adenylyl cyclase (Shuttleworth & Thompson, 1999), on native C6-2B glioma cells (Chiono et al, 1995;Fagan et al, 1998), on bovine adrenal glomerulosa cells (Burnay et al, 1998) and on mouse parotid acini (Watson et al, 1998) that it is Ca 2+ entry via capacitative entry channels which produces signi®cant modulation of cyclic AMP accumulation.…”
Section: Casupporting
confidence: 90%
“…The marked reduction of the inhibitory action of thapsigargin in the absence of added Ca 2+ and in the presence of EGTA indicates that Ca 2+ released from intracellular stores plays only a minor role in inhibition of cyclic AMP accumulation, at most. This is consistent with the conclusion drawn from experiments on HEK 293 cells transfected with the type VI (Cooper et al, 1994) and type VIII adenylyl cyclase (Shuttleworth & Thompson, 1999), on native C6-2B glioma cells (Chiono et al, 1995;Fagan et al, 1998), on bovine adrenal glomerulosa cells (Burnay et al, 1998) and on mouse parotid acini (Watson et al, 1998) that it is Ca 2+ entry via capacitative entry channels which produces signi®cant modulation of cyclic AMP accumulation.…”
Section: Casupporting
confidence: 90%
“…-sensitive ACs to CCE over other types of Ca 2+ increase that have been observed in a number of cell types (Burnay et al, 1998;Debernardi et al, 1993;Fagan et al, 2000a;Fagan et al, 1998;Shuttleworth and Thompson, 1999;Watson et al, 1998;Yoshimura and Cooper, 1992). It has been hypothesized that this property might, at least, partially, reflect the residence of these ACs in lipid-raft regions of the PM alongside sites of CCE (Fagan et al, 2000b;Smith et al, 2002).…”
Section: +mentioning
confidence: 96%
“…Muscarinic augmentation of stimulated cAMP accumulation, resulting in potentiation of amylase release (20), has also been shown to involve capacitative Ca 2ϩ entry in mouse parotid acini (1), and data obtained demonstrated that Ca 2ϩ entry plays an important role in promoting AC synthesis. These data, combined with findings that AC8 is expressed in mouse parotid acini (1) and that Ca 2ϩ /CaM stimulates AC and augments the effects of forskolin on cyclase activity in membrane fractions and intact cells (21,22), are consistent with results obtained in HEK 293 cells expressing AC8 (8,11).…”
mentioning
confidence: 96%
“…To date, 10 different ACs, 1 each with distinct regulatory properties, have been cloned; their existence suggests that they may be differentially regulated. The enzymes exhibit type specific stimulatory and inhibitory regulation by G-protein ␣ and ␤␥ subunits, Ca 2ϩ , CaM, forskolin, P-site inhibitors, protein kinases A and C (PKC) (2)(3)(4)(5)(6), and calcineurin (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation